Cardiac thrombus hamster - case report - Silva, P. S. P.; Dias, F. P.; Dullius, J. L.; Cruz, G. D. (Scientific Electronic Archives, 2017)
A thrombus is formed by a change caused by Virchow’s triad, may be associated or not to an infectious process resulting in sepsis and causing primarily to systemic inflammatory response syndrome (SIRS). A syrian hamster (Mesocricetus auratus) came to death at the Veterinary Hospital of University of Santo Amaro came and forwarded to the Anatopatologia Animal service, where the necropsy was performed and visualized ascites, hydrothorax and thrombotic formation in the right atrium. On histopathologic examination, it was observed the presence of a thrombus presence with leukocytes, bacterium and necrotic material. Â